Clinical and Radiological Features of Urachal Carcinoma and Infection - Li, Shichao; Meng, Xiaoyan; Liang, Ping; Feng, Cui; Shen, Yaqi; Hu, Daoyu; Li, Zhen (Frontiers in Oncology, 2021)
Purpose To explore the clinical and radiological differences between urachal carcinoma and urachal infection. Methods Clinical and imaging information for 13 cases of urachal carcinoma and 14 cases of urachal infection confirmed by pathology were retrospectively analyzed. The size, location, shape, margin, lesion composition, calcification, T1 and T2 signal intensity, peripheral lymph nodes, degree of enhancement, adjacent bladder wall, and apparent diffusion coefficient (ADC) value were examined in both groups, and distinguish features were determined. test and student t-test were used for statistical analysis. The student t-test or Mann-Whitney U test was used for quantitative data, and Fisher's exact test was used for qualitative data. Kappa coefficient consistency test was used to evaluate the interobserver agreement. Results Sex, hematuria, abdominal pain, calcification and adjacent bladder wall thickened can distinguish between urachal carcinoma and urachal infection (p < 0.05). There were no statistical differences in age (p = 0.076), size (p = 0.797), location (p = 0.440), shape (p = 0.449), margin (p = 0.449), lesion composition (p = 0.459), T1 signal intensity (p = 0.196), T2 signal intensity (p = 0.555), peripheral lymph nodes (p = 0.236), degree of enhancements (p = 0.184) and ADC value (p = 0.780) between two groups. Conclusion The following clinical and imaging features are helpful for distinguishing urachal carcinoma from urachal infection: sex, hematuria, abdominal pain, calcification, and thickening of the adjacent bladder wall.